2007
DOI: 10.1158/1055-9965.epi-07-0229
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Exposure in Public Places in Guatemala: Comparison with other Latin American Countries

Abstract: Objective: To measure secondhand smoke levels in workplaces in Guatemala and to compare exposure to levels in other Latin American cities. Methods: Exposure was estimated by passive sampling of vapor phase nicotine using a filter badge. Filters were placed in 1 hospital, 1 school, 2 universities, 1 government building, the airport, and 10 restaurants/ bars. In total, 103 filters were deployed (plus 7 duplicates and 10 blanks). Nicotine (Mg/m 3 ) was measured by gas chromatography. Medians [interquartile ranges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 18 publications
(27 reference statements)
3
28
0
Order By: Relevance
“…A pioneering study that measured airborne nicotine concentrations in 22 hospitals in seven European cities (Vienna (Austria), Paris (France), Athens (Greece), Florence (Italy), Porto (Portugal), Barcelona (Spain) and Ö rebro (Sweden)) during 2001-2002 showed low but detectable SHS exposure in hospitals [5,18,19]. Similar surveys conducted in 11 Latin American countries and China, including one hospital in each country between 2002 and 2006, also showed low but quantifiable nicotine concentrations [20][21][22][23]. In a previous study in Catalonia, Spain, low levels of airborne nicotine were found in 44 public hospitals before the new Spanish tobacco control law came into force in 2006, which subsequently mostly decreased to unquantifiable concentrations after the ban [6].…”
Section: Discussionmentioning
confidence: 81%
“…A pioneering study that measured airborne nicotine concentrations in 22 hospitals in seven European cities (Vienna (Austria), Paris (France), Athens (Greece), Florence (Italy), Porto (Portugal), Barcelona (Spain) and Ö rebro (Sweden)) during 2001-2002 showed low but detectable SHS exposure in hospitals [5,18,19]. Similar surveys conducted in 11 Latin American countries and China, including one hospital in each country between 2002 and 2006, also showed low but quantifiable nicotine concentrations [20][21][22][23]. In a previous study in Catalonia, Spain, low levels of airborne nicotine were found in 44 public hospitals before the new Spanish tobacco control law came into force in 2006, which subsequently mostly decreased to unquantifiable concentrations after the ban [6].…”
Section: Discussionmentioning
confidence: 81%
“…Increasing evidence also indicates that SHS can infiltrate from separated smoking into nonsmoking areas in multifamily dwellings (Bohac, Hewett, Hammond, & Grimsrud, 2011;King, Travers, Cummings, Mahoney, & Hyland, 2010;Kraev, Adamkiewicz, Hammond, & Spengler, 2009). Furthermore, air monitoring results (using particulate matter [PM] and airborne nicotine levels as SHS markers) have consistently proven the industry's "accommodation program" and partial smoking restrictions to be ineffective in bars, restaurants, and casinos (Agbenyikey et al, 2011;Akbar-Khanzadeh, Milz, Ames, Spino, & Tex, 2004;Barnoya, Mendoza-Montano, & Navas-Acien, 2007;Erazo et al, 2010;Jiang et al, 2011;Kim, Sohn, & Lee, 2010;Lambert, Samet, & Spengler, 1993;Milz et al, 2007;Repace, 2009;Repace et al, 2011).…”
Section: Ineffective Alternatives To Shs Exposure Hazardsmentioning
confidence: 99%
“…The most widely used methods for determining SHS exposure in indoor public places and workplaces are airborne nicotine and PM <2.5 µm (PM2.5) (Barnoya et al, 2007;Hyland, Travers, Dresler, Higbee, & Cummings, 2008;Liu et al, 2010;Lopez et al, 2008;Navas-Acien et al, 2004;Nebot et al, 2005). Airborne SHS studies generally measure nicotine for several days, reflecting time-weighted average concentrations over the period of assessment.…”
Section: Environmental Measures Of Shsmentioning
confidence: 99%
See 2 more Smart Citations